2019
DOI: 10.1098/rstb.2018.0430
|View full text |Cite
|
Sign up to set email alerts
|

Brain stimulation to left prefrontal cortex modulates attentional orienting to gaze cues

Abstract: In social interactions, we rely on non-verbal cues like gaze direction to understand the behaviour of others. How we react to these cues is determined by the degree to which we believe that they originate from an entity with a mind capable of having internal states and showing intentional behaviour, a process called mind perception . While prior work has established a set of neural regions linked to mind perception, research has just begun to examine how mind perception affects social-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 136 publications
(252 reference statements)
1
8
0
Order By: Relevance
“…Work on gaze cueing has provided support for this assumption. For example, Wiese, Wykowska, Zwickel, and Muller [ 48 ] found that when observers believed an agent has intention, larger attention shifts occurred compared to when observers did not have this belief (see also, [ 49 , 50 ]). It is also the case, however, that a face exhibiting fear does not reliably induce greater cueing effects relative to a neutral face [ 16 , 51 , 52 ].…”
Section: Representation Rather Than Functionmentioning
confidence: 99%
“…Work on gaze cueing has provided support for this assumption. For example, Wiese, Wykowska, Zwickel, and Muller [ 48 ] found that when observers believed an agent has intention, larger attention shifts occurred compared to when observers did not have this belief (see also, [ 49 , 50 ]). It is also the case, however, that a face exhibiting fear does not reliably induce greater cueing effects relative to a neutral face [ 16 , 51 , 52 ].…”
Section: Representation Rather Than Functionmentioning
confidence: 99%
“…The penultimate piece in this section is a transcranial direct current stimulation (tDCS) study by Wiese et al [22], which aimed to examine the role played by key brain regions involved in social perception when an observed agent is perceived as having a mind (human) or not (robot). The authors used a social attention gaze cueing paradigm featuring a human or a robot face, while tDCS was applied over prefrontal and temporo-parietal brain regions.…”
Section: Robots As a Tool To Study Social Cognitionmentioning
confidence: 99%
“…Similar effects of mind perception on human-nonhuman interaction can also be found in behavioral studies, such that increased mind perception is associated with improvements in social-cognitive processing (e.g., Abubshait & Wiese, 2017; Caruana, de Lissa, & McArthur, 2015Wykowska, Wiese, Prosser, & Müller, 2014;Wiese, Wykowska, Zwickel & Mueller, 2012). There is also evidence that variation in activation in prefrontal social brain areas, such as the left vmPFC, can be linked to variations in social-cognitive performance (Wiese, Abubshait, Azarian, & Blumberg, 2019;Wiese et al, 2018): using fMRI and tDCS stimulation, it was shown that the degree to which gaze signals (or cues) were followed differently as a function of brain activation in left vmPFC associated with mind perception.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we asked participants to perform a gaze cueing task with a human and a robot gazer that requires them to respond as quickly and accurately as possible via key press to targets (i.e., letter F or T) that are either looked at (i.e., valid trials) or looked away from (i.e., invalid trials) by either of the agents, which typically results in faster reaction times on valid versus invalid trials (with the difference in reaction times (RT) being referred to as gaze-cueing effect; Friesen & Kingstone, 1998). The gaze cueing task is performed twice during the experiment, once before brain stimulation is applied to acquire baseline gaze following effects per participant for the human and the robot gazer, and once under tDCS stimulation to brain areas that have previously been linked to mind perception, namely left prefrontal areas (PFA), and brain areas that have not been linked to mind perception in previous studies, namely left temporo-parietal areas as an active control condition (TPA; Wiese et al, 2018;2019). Participants were classified as Human Gaze Followers (HGF) if their baseline gaze cueing effects were larger for the human than robot agent, or as Robot Gaze Followers (RGF) if their baseline gaze cueing effects were larger for the robot than human agent.…”
Section: Introductionmentioning
confidence: 99%